Effect of the incorporation of sugarcane bagasse fibers in asphalt mixture dosed by the Superpave method (Research, Society and Development, 2021)
Sugar industry waste bagasse contains many natural fiber materials, and the application of natural fibers in asphalt mixes such as SMA (Stone Matrix Asphalt) has become an attractive alternative for the construction of flexible pavements. This study aims to evaluate the mechanical performance of an asphalt mixture modified by incorporating 0.3% sugarcane bagasse fiber and with a size of 20 mm. The asphalt binder was submitted to penetration, softening point, and rotational viscosity tests to carry out this research, and the aggregates were characterized by specific mass, particle size, and absorption tests. Furthermore, the Superpave dosage was performed to produce the specimens to be evaluated in the splitting tensile strength test, resilient modulus, Marshall stability, and draindown sensitivity. As a result, the modified asphalt mixture presented a better performance in all evaluated strength tests and the leakage content within the standard specifications. Therefore, according to this, re-search, sugarcane bagasse fibers proved to be a viable alternative for SMA-type mixtures. Thus, the application of this material in asphalt paving and improving some essential characteristics can significantly reduce the environmental impacts generated by the inadequate disposal of these residues by sugar mills.